Rapid synthesis of MgCo2O4 and Mg2/3Ni4/3O2 nanocrystals in supercritical fluid for Mg-ion batteries. Issue 63 (11th November 2019) - Truong, Quang Duc; Kobayashi, Hiroaki; Honma, Itaru
Abstract : High-quality spinel MgCo2 O4 and rocksalt Mg2/3 Ni4/3 O2 nanocrystal cathodes allow fast extraction/insertion of magnesium ions for high energy-density batteries. Abstract : Magnesium metal complex oxides are potential electrode materials for magnesium ion batteries with high specific capacities. However, the strong electrostatic interaction between Mg 2+ and the host lattice due to its divalency induces slow intercalation kinetics of Mg ions within the crystal lattices. Thus, nanocrystalline particles with shortened Mg ion diffusion distance enable the insertion/extraction of Mg ions and improve the specific capacities of the batteries. Herein, we report the facile rapid production of crystalline MgCo2 O4 and Mg2/3 Ni4/3 O2 nanocrystals by rapid supercritical fluid processing. The phase transition from spinel to rocksalt during the Mg 2+ ion intercalation has been confirmed by high-resolution transmission electron microscopy. The nanosheets of Mg2/3 Ni4/3 O2 rocksalt nanocrystals were controllably synthesized for the first time, which are active materials for magnesium-ion batteries.